Indonesia Islamic students' belief towards the performance of artificial intelligence: perceptions, impacts, and anticipations - Yuni Sugiarti; Ence Oos Mukhamad Anwas; Fitroh Fitroh; Janu Arlinwibowo; Ihsan Maulana Anwas (IAES International Journal of Artificial Intelligence (IJ-AI), 2026)
This research aims to i) determine the belief level of Islamic university students towards AI for learning and ii) what factors related to student confidence in using AI for learning. This study employed a mixed-methods sequential explanatory design. The research subjects were students of the strata 1, Universitas Islam Negeri Syarif Hidayatullah, and students of Universitas Islam Negeri Sunan Kalijaga, totaling 411 students. The research sample was obtained using random techniques. The quantitative data collection method is questionnaire-based, and data in-depth analysis is carried out qualitatively using the focus group discussion (FGD) technique. The quantitative data analysis method was carried out using descriptive statistics, and the qualitative study was carried out thematically. This research found that the majority of students have a high level of confidence in the performance of artificial intelligence (AI) as a tool for them. This level of belief is significantly and positively related to understanding of the AI platform used, lecturer support and guidance, parental support and guidance, and support from fellow students. However, belief in AI cannot be absolute because it is feared that it will result in poor use. AI platform users, especially students, lecturers, researchers, and anyone who uses it, need to recheck and deepen its accuracy and correctness.